Behaviour of composite beam arranged as boxed-section with C-channel of cold-formed steel of lipped section - Khadavi, Khadavi (2020)
Cold formed steel (CFS) of lipped C-Channel sections are commonly use because of their simple forming procedures and easy to erect. To improve the flexural strength of the proposed composite beam, the C-channel of Lipped section is arranged toe-to-toe to form into boxed shape section and filled with self-compacting concrete (SCC). Reinforcement bars was used in a tension zone to increase the flexural strength of the proposed beam in this experimental study. A U-shape re-bars was installed to act as shear connections between concrete slab and beam of boxed section filled with self-compacting concrete. Two specimens were prepared and tested until failure. A C-channel section of size 250mm deep, 75mm width, and 2.4mm thick was used for the proposed composite beam section. Longitudinal rebar's size of 16mm and 20mm were installed at the bottom of the beam encased by the self-compacting concrete of 50MPa. A U-shape re-bar if size 12mm in diameter was used as a shear connector and functioned as vertical shear resistance for the beam system. The beam is kept restrained in position by a profiled metal decking installed on top of the beam to form a slab system also cast using by SCC. The specimens were tested under pure bending arranged as simply supported beams. It was found that the moment resistance of the experimental results agreed well with the predicted numerical analysis.